PENILAIAN KEPUASAN PENGGUNA TERHADAP ATRIBUT PRODUK DENGAN MENGGUNAKAN MODEL KANO; STUDI KASUS DESAIN INKUBATOR BAYI - Tarigan, Ukurta; Ginting, Rosnani (TALENTA Publisher, 2018)
A Newborns need special attention because it takes time to adapt to the outside world. In accordance with the standard post-neonatal procedures, newborns should be incorporated into the incubator within a certain period of time according to the infant's health level. Infant incubator as a medical device used to care for newborns, often get complaints from doctors and child nurses. The complaint indicates consumer dissatisfaction with infant incubator products in the hospital. Broadly speaking, complaints against infant incubators lie in inappropriate designs. To overcome these complaints the researchers apply the method of Kano to determine the satisfaction frome every technical characteristics. Through the mapping can be seen that from the seven attributes that become the question, there are two attributes that are in the category of Attractive namely